Genomic signatures of ecological divergence between savanna and forest populations of a Neotropical tree - Muniz, André Carneiro; de Oliveira Buzatti, Renata Santiago; de Lemos-Filho, José Pires; Heuertz, Myriam; Nazareno, Alison Gonçalves; Lovato, Maria Bernadete (Annals of botany, 2023)
Abstract Background and Aims In eastern Neotropical South America, the Cerrado, a large savanna vegetation, and the Atlantic Forest harbour high biodiversity levels, and their habitats are rather different from each other. The biomes have intrinsic evolutionary relationships, with high lineage exchange that can be attributed, in part, to a large contact zone between them. The genomic study of ecotypes, i.e. populations adapted to divergent habitats, can be a model to study the genomic signatures of ecological divergence. Here, we investigated two ecotypes of the tree Plathymenia reticulata, one from the Cerrado and the other from the Atlantic Forest, which have a hybrid zone in the ecotonal zone of Atlantic Forest–Cerrado. Methods The ecotypes were sampled in the two biomes and their ecotone. The evolutionary history of the divergence of the species was analysed with double‐digest restriction site‐associated DNA sequencing. The genetic structure and the genotypic composition of the hybrid zone were determined. Genotype-association analyses were performed, and the loci under putative selection and their functions were investigated. Key Results High divergence between the two ecotypes was found, and only early-generation hybrids were found in the hybrid zone, suggesting a partial reproductive barrier. Ancient introgression between the Cerrado and Atlantic Forest was not detected. The soil and climate were associated with genetic divergence in Plathymenia ecotypes and outlier loci were found to be associated with the stress response, with stomatal and root development and with reproduction. Conclusions The high genomic, ecological and morphophysiological divergence between ecotypes, coupled with partial reproductive isolation, indicate that the ecotypes represent two species and should be managed as different evolutionary lineages. We advise that the forest species should be re-evaluated and restated as vulnerable. Our results provide insights into the genomic mechanisms underlying the diversification of species across savanna and forest habitats and the evolutionary forces acting in the species diversification in the Neotropics.